ANALISIS SEMIOTIK ATAS SAMPUL MAJALAH TEMPO JAKARTA "RIZAL RAMLI PETARUNG ATAU PERAUNG" - Yusra, Wildan; Hafiar, Hanny; Sjoraida, Diah Fatma (Informasi, 2017)
This study uses qualitative methods with semiotics analysis from Charles SandersPeirce. The purposes of this study are to determine the symbol contained in MBM Tempo,the meaning contained within the symbol, and how these symbols constructing RizalRamli's Image as the howling. The result of this study showed MBM Tempo Jakarta cover"The Fighter or The Howling" 24-30 August 2015 Edition consist of three main symbols,Rizal Ramli's on his hips, pointing and opened mouth, a hand hold puppet stick, andtext symbol. Rizal Ramli's caricature in the cover of MBM Tempo is an illustration ofthe text is written in the middle of Tempo's cover, so that both are interlocked. Thesesymbols have different meanings. The meaning of each symbol constructing the imageof Rizal Ramli as the howling in the cover of MBM Tempo. The conclusion of this studyshowed that the symbols MBM Tempo Jakarta cover "The Fighter or The Howling" 24-30August 2015 Edition consist of three main symbols, Rizal Ramli's on his hips, pointingand opened mouth, a hand hold puppet stick, and text symbol included to typography.AbstrakPenelitian ini menggunakan metode kualitatif dengan analisis semiotika CharlesSanders Peirce. Tujuan penelitian ini adalah untuk mengetahui simbol yang terdapatdalam MBM Tempo, makna yang terkandung dalam simbol-simbol, dan simbol padaMBM Tempo dapat mengkonstruksi citra Rizal Ramli sebagai Peraung. Hasil penelitianmenunjukkan sampul MBM Tempo Jakarta "Rizal Ramli Petarung atau Peraung"Edisi 24-30 Agustus 2015 terdiri dari tiga simbol utama, simbol gesture Rizal Ramlisedang berkacak pinggang, menunjuk dan mulut terbuka, simbol tangan wayang yangmemegang tuding, dan simbol teks. Karikatur Rizal Ramli yang terdapat dalam sampulMBM Tempo merupakan ilustrasi dari teks yang tertulis ditengah sampul Tempo,sehingga keduanya saling berkaitan. Simbol-simbol tersebut memiliki makna yangberbeda-beda. Makna yang terkandung dari setiap simbol mengkonstruksikan citraRizal Ramli sebagai Peraung dalam sampul MBM Tempo. Kesimpulan penelitian iniadalah terdapat tiga simbol utama dalam sampul MBM Tempo Jakarta "Rizal RamliPetarung atau Peraung" Edisi 24-30 Agustus 2015, yaitu simbol gesture Rizal Ramlisedang berkacak pinggang, menunjuk, dan mulut terbuka, simbol tangan wayang yangmemegang tuding, dan simbol teks yang termasuk tipografi.